2017
DOI: 10.3390/rs9050410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MODIS Land Surface Temperature Data to Estimate Near-Surface Air Temperature in Northeast China

Abstract: Air temperature (T air ) near the ground surface is a fundamental descriptor of terrestrial environment conditions and one of the most widely used climatic variables in global change studies. The main objective of this study was to explore the possibility of retrieving high-resolution T air from the Moderate Resolution Imaging Spectroradiometer (MODIS) land surface temperature (LST) products, covering complex terrain in Northeast China. The All Subsets Regression (ASR) method was adopted to select the predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 55 publications
4
54
0
3
Order By: Relevance
“…Since available, MODIS LST data has been used for various studies, such as evaluating and monitoring urban heat islands [11][12][13][14][15], estimating air surface temperatures (Ta) [16][17][18][19], retrieving soil moisture [20,21], drought assessment [22], and hydrology applications [23]. Most of these studies have shown that the changes of land surface properties (e.g., normalized difference vegetation index (NDVI), elevation, and land use/cover types) will result in the variations of LST [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since available, MODIS LST data has been used for various studies, such as evaluating and monitoring urban heat islands [11][12][13][14][15], estimating air surface temperatures (Ta) [16][17][18][19], retrieving soil moisture [20,21], drought assessment [22], and hydrology applications [23]. Most of these studies have shown that the changes of land surface properties (e.g., normalized difference vegetation index (NDVI), elevation, and land use/cover types) will result in the variations of LST [3].…”
Section: Introductionmentioning
confidence: 99%
“…This study employed the level 3 MODIS eight-day tiled land surface temperature (LST) product. Previous studies have shown that MODIS LST exhibited a high correlation with the near-surface air temperature as recorded by weather stations (e.g., [33][34][35]). The period of the thaw was identified when mean daily LST was exceeded 0 • C. Although the LST data used in this study was the eight-day product, some null values were included due to poor weather conditions.…”
Section: Remote Sensing Datamentioning
confidence: 91%
“…Resultados semelhantes aos observados neste estudo foram obtidos por Yang et al (2017) que estimaram a temperatura do ar anual no Nordeste da China, cujo resultado do erro REQM foi de 4,63 °C para a temperatura máxima; de 3,99 °C para a temperatura mínima e de 3,60 °C para a temperatura média do ar. Nessa mesma linha, os modelos obtidos por Cristóbal et al (2008) para estimar a temperatura do ar diária, mensal e anual para o Nordeste da Península Ibérica e para a Catalunha, apresentaram REQM variando entre 0,65 e 1,69 °C para a temperatura média, entre 1,06 e 2,64 °C para a temperatura mínima e entre 0,86 e 2,36 °C para a temperatura máxima do ar.…”
Section: Validação Dos Modelosunclassified
“…Para contornar as limitações decorrentes da falta destes registros, diferentes métodos têm sido estudados a fim de se obter maior exatidão nas estimativas de dados ausentes. Dentre eles, destacam-se aqueles baseados nos princípios da estatística clássica e geoestatística (VIOLA et al, 2010;PERIN et al, 2015), inteligência artificial (VENTURA et al, 2013;DEPINÉ et al, 2014), lógica fuzzy (FERREIRA, 2012), sensoriamento remoto (ZHANG et al, 2015;YANG et al, 2017) e também a regressão múltipla. Particularmente para este último, o qual tem sido utilizado intensamente, em função de sua simplicidade, diversos trabalhos têm sido conduzidos em várias regiões brasileiras, a exemplo de Minas Gerais e Pará (FERREIRA et al, 2006), São Paulo (PANTANO; BARDIN, 2012), Rio Grande do Sul (CARGNELUTTI FILHO et al, 2008) e estados da região nordeste (MEDEIROS et al, 2005).…”
Section: Introductionunclassified